An Index to Measure Rural Diversity in the Light of Rural Resilience and Rural Development Debate - Quaranta Giovanni; Salvia Rosanna (European Countryside, 2014)
Diversity has been extensively studied in ecological systems and its relationship with resilience has been well recognized. In social and ecological systems, in fact, diversity is considered key to determining resilience where resilience is defined as system’s capacity to learn and adapt in the face of internal or external perturbations. However, although human and ecological systems are dynamic, interacting and interdependent, little attention has been given to social systems diversity and its implications. The interest in diversity and resilience of social-ecological systems is increasingly growing, particularly in the rural contexts, due to its possible effects on social and economic development and livelihoods. In this paper we define an analytical tool, the Rural Diversity Index (RDI), to assess the role of natural, economic and social diversity in determining alternative rural socio-ecological developmental patterns. The application of the RDI in pilot areas of Southern Italy showed that, in specific socio-ecological systems, higher natural-socio-economic diversity leads to higher degree of rural development, as measured through standard socio-economic indicators.